Pengaruh Pemahaman Perpajakan, Kualitas Pelayanan Pajak Dan Sanksi Pajak Terhadap Motivasi Wajib Pajak Orang Pribadi Dalam Membayar Pajak Pada Kpp Pratama Surabaya Gubeng - Fauziah Nursya’bani Fadillah; Tries Ellia Sandari (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This study aims to test and analyze the effect of understanding taxation, the quality of tax services and tax sanctions on the motivation of individual taxpayers in paying taxes at KPP Pratama Surabaya Gubeng. In this study using quantitative methods using primary data obtained from questionnaires. The population in this study were taxpayers registered at KPP Surabaya Gubeng. Sampling using purposive sampling technique and the sample size in this study was 100 respondents using the Slovin formula. Data analysis using SmartPLS. The results of this study indicate that service quality and tax sanctions have a positive and significant effect on motivation to pay taxes. Meanwhile, understanding taxation has no effect on motivation to pay taxes.